SOCIAL AND ECONOMIC LIFE OF STREETS SWEEPERS WOMEN IN THE UNIVERSITY BENGKULU ENVIRONTMENT - Fitri, Wiki Antika; Rahmat, Agus Zainal; Parlan, Parlan (UNIB Press, 2016)
Abstract: The purpose of this study is to determine the social life, economic life, and community responses to the socio-economic life of sweeping Streets women in the environtment of University of Bengkulu. The type of this research is descriptive-qualitative research. Data were collected through interviews, observation and documentation. The examination of the validity of the data using the triangulation of subjects, triangulation of time, and triangulation of techniques. The results showed: (a) discipline of work, discipline is very important in the work undertaken, both the discipline of time, and the discipline of responsibility. (b) work and time, the street sweeper woman can divide her time between work at home and work as a street sweeper. (c) the reason to work as a street sweeper is more likely to increase the family's economic income. This research recommends that street sweepers can more time divide their jobs and responsibilities as housewives for the education of their children, as the work becomes a temporary sweeper. Stree ts sweeper organizers to pay more attention to the economic conditions of families with the salary or wages of the existing UMP in the province of Bengkulu.